Deep Learning and Computer Vision for Visual Security Monitoring in DevOps Environments (Journal of Artificial Intelligence Research, 2023)
The integration of deep learning and computer vision technologies has become increasingly significant in enhancing visual security monitoring within DevOps environments. With the rapid digitization of IT systems and data centers, traditional security measures often fall short in addressing the complexities and threats posed by cyber-attacks. This paper discusses the application of deep learning models in automating threat detection by analyzing visual data streams generated from surveillance systems. By leveraging advanced algorithms, DevOps teams can enhance situational awareness, quickly identify anomalies, and respond to potential threats effectively. The discussion includes methodologies for implementing these technologies, the challenges faced, and potential future developments in visual security monitoring. The paper aims to provide insights into how DevOps teams can harness the power of deep learning and computer vision to create more secure and resilient IT environments.
Keywords: Deep learning; computer vision; visual security monitoring; DevOps; threat detection